The effect of Competitive StrategyandTotal Quality Management (TQM) to the Project Management of Continuous Improvement at PT Riau Prima Energi, Division of Power Generating RAPP - Nasution, Sya’ral; Hendriani, Susi; Samsir, Samsir (Program Pascasarjana, Universitas Riau, 2016)
The purpose of this study was to explore the relationship between competitive strategy, total quality management (TQM), and the continuous improvement of project management on PT Riau Prima Energi in the Power Plant industry in the City of PangkalanKerinci of PelalawanDistrict. PT. Riau Prima Energi. This research explains “Differentiation Strategy” has stronger influenced toward TQM elements rather than “Cost Leadership Strategy”. This study also findthat no direct relationship between Differentiation Strategy and employee relations to make project management of continual improvement successful.Tcompanyneed to pay attention on aspects such of employee empowerment, reward and compensation system, as well as open communication, accompanied by a comprehensive training system to achieve good performance of continual improvement of project management.